Adsorption study of cadmium ions on kaolinite modified by histidine and cysteine - Mladenović Nataša N.; Ivanović Marija M.; Kljajević Ljiljana M.; Gulicovski Jelena J.; Nenadović Snežana S.; Trivunac Katarina V. (Tehnika, 2019)
Continuous development of new technologies leads to increasing pollution of water, thus creating the need for new materials that could be used in the processes of its purification. Therefore, adsorbents prepared from agricultural waste, resins, silica gels, zeolites, clays, flying ash, aluminosilicates and other materials are being investigated as potential sorbents. Recently, research has focused on improving the adsorption capacity by modifying the material by binding or impregnating inorganic and organic molecules on the surface. In this paper, the kaolinite modification with amino acids, histidine and cysteine, was performed to improve the efficiency of adsorption of cadmium ion. Cation exchange capacity (CEC) of raw and modified kaolinite was determined by titration with methylene blue. The influence of operating parameters, such as adsorption time, pH value of the solution, initial metal concentration and temperature, on the capacity and adsorption efficiency were examined. Better agreement of experimental results with Freundlich's adsorption isotherm and the pseudo-second order kinetics model suggest that the adsorption of cadmium ions on the investigated adsorbents takes place by chemisorption mechanism. The change of Gibbs free energy has a negative value for both adsorbents, which shows that the adsorption process is spontaneous. The efficacy of cadmium removal from the aqueous solution onto histidine-modified kaolinite increased from 78.6% to 91.8%.